2007
DOI: 10.1177/1076029607306807
|View full text |Cite
|
Sign up to set email alerts
|

Activated Protein C Resistance and Factor V Leiden in Mexico

Abstract: A common cause of hereditary thrombophilia is activated protein C resistance (APCR), and most cases result from factor V Leiden mutation. An APCR phenotype without association with factor V Leiden has been described. This transversal, observational, nonrandomized study evaluated these 2 phenomena in healthy indigenous and mestizo Mexican subjects (n = 4345), including 600 Mexican natives. No indigenous subjects had APCR, but 82 mestizo subjects did. After retesting, 50 subjects had a negative test. The remaini… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
8
0

Year Published

2010
2010
2022
2022

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 49 publications
1
8
0
Order By: Relevance
“…Our study shows, as was found by Majluf-Cruz et al (2008), that the Leiden factor V polymorphism is not very common in our population, as we did not find it in any of the patients, their mothers, or controls. Recently, our group with different patients found the same (Zavala Hernández et al, 2010).…”
Section: Discussionsupporting
confidence: 75%
See 1 more Smart Citation
“…Our study shows, as was found by Majluf-Cruz et al (2008), that the Leiden factor V polymorphism is not very common in our population, as we did not find it in any of the patients, their mothers, or controls. Recently, our group with different patients found the same (Zavala Hernández et al, 2010).…”
Section: Discussionsupporting
confidence: 75%
“…In Mexico, there are two studies: one mentioning high prevalence (Ruiz-Argü elles et al, 2005) and the other, the opposite (Majluf-Cruz et al, 2008).…”
Section: Introductionmentioning
confidence: 99%
“…We searched PubMed using the terms related to VTE [Mesh Terms] (venous thrombosis, venous thromboembolism, deep vein thrombosis, pulmonary embolism, or thrombophilia) and the terms related to genetics [Title/Abstract] (genetic, genetics, mutation, mutations, polymorphism, polymorphisms, variant, variants, variation, variations, SNP, SNPs, GWAS, GWA study, GWA studies, genome wide, protein C deficiency, protein S deficiency, antithrombin deficiency, thrombomodulin, factor V Leiden, FV Leiden, factor V G1691A, factor II G20210A, or prothrombin G20210A). lation has been elucidated (30)(31)(32)(33)(34)(35)(36)(37)(38)(39)(40)(41)(42)(43)(44)(45)(46). On average, the allele frequency of FV Leiden is estimated to be 3.5 % in Europe (47).…”
Section: Introductionmentioning
confidence: 99%
“…The risk for thrombosis increases in the presence of multiple thrombophilic defects [3]. Hereditary thrombophilic factors and their frequencies exhibit some variations in different populations or patient groups [4][5][6][7][8]. Ischemic stroke (IS) is usually associated with arterial diseases (e.g.…”
Section: Introductionmentioning
confidence: 99%